A Study of 408 Cold Thyroid Nodules in a Country with Endemic Goitre - Koutras, D. A.; Livadas, D.; Sfontouris, J.; Messaris, G.; Statherou, P. K. (Nuklearmedizin - NuclearMedicine, 1968)
408 cases of single thyroid nodules, scintigraphically cold, were operated and examined histologically. Malignancy was proved in 53 (13%) of them. The incidence of malignant neoplasms was twice higher in males (23.4%) than in females (11.6%), and four times higher in persons more than 60 years old (46.4%) than in the younger age groups. It is concluded that the incidence of malignancy in single cold nodules of the thyroid is high, even in centres drawing most of their case material from regions with endemic goitre, and for this reason surgical removal is recommended.